Antroduodenal motility in neurologically handicapped children with feeding intolerance - Werlin, Steven L (BioMed Central, 2004)
BACKGROUND: Dysphagia and feeding intolerance are common in neurologically handicapped children. The aim is to determine the etiologies of feeding intolerance in neurologically handicapped children who are intolerant of tube feedings. METHODS: Eighteen neurologically handicapped children, followed in the Tube Feeding Clinic at the Children's Hospital of Wisconsin who were intolerant of gastrostomy feedings. The charts of these 18 patients were reviewed. Past medical history, diagnoses, history of fundoplication and results of various tests of gastrointestinal function including barium contrast radiography, endoscopy and antroduodenal manometry were documented. RESULTS: Five of 11 children had abnormal barium upper gastrointestinal series. Seven of 14 had abnormal liquid phase gastric emptying tests. Two of 16 had esophagitis on endoscopy. All 18 children had abnormal antroduodenal motility. CONCLUSIONS: In neurologically handicapped children foregut dysmotility may be more common than is generally recognized and can explain many of the upper gastrointestinal symptoms in neurologically handicapped children.